1984
DOI: 10.3109/07420528409059113
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Circumnutation Movement of the Shoots in Phaseolus Vulgaris L

Abstract: The apex of growing stems in twining plants describes a rhythmic movement in space called circumnutation. By the method of orthogonal projections, the position in space of the apex can be determined constantly. The mathematical analysis of data allowed us to determine that for Phaseolus vulgaris L. (cv. Mangetout Blanc de Juillet) grown under constant illumination and temperature (25 degrees C) the period is about 100 min. This movement has been related to rhythmic changes in the osmotic potential of the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…Others have also separated overall growth from changes in growth that lead to nutations. For instance, NPA inhibited nutations but had a small effect on growth in stems of pea (Britz and Galston, 1983), and lithium chloride prevented nutations but did not alter growth in Phaseolus vulgaris shoots (Millet et al, 1984). This supports the assertion that, whereas nutations require growth, growth does not require nutations.…”
Section: Discussionsupporting
confidence: 62%
“…Others have also separated overall growth from changes in growth that lead to nutations. For instance, NPA inhibited nutations but had a small effect on growth in stems of pea (Britz and Galston, 1983), and lithium chloride prevented nutations but did not alter growth in Phaseolus vulgaris shoots (Millet et al, 1984). This supports the assertion that, whereas nutations require growth, growth does not require nutations.…”
Section: Discussionsupporting
confidence: 62%
“…For example, a 100-min (Millet et al, 1984) or a 2-4-h (Koukkari, 1994) period of circumnutational movement is observed in shoots of climbing bean; moreover, cycles of 45-120 min in shoot elongation rates in radish, cucumber, and sunflower (Kristie and Jolliffe, 1986) and cycles of 112-133 min in soybean (Kurt et al, 1998) have been reported. In roots, circumnutational cycles of 1-2 h have been reported in Kentucky blue grass (Fisher, 1964), and cycles ranging from 12 min to 1 h have been reported in maize (Walter et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…An oscillator with a period of 3 hr, for example, could couple with the stomatal and photosynthetic rhythms every eight periods and with the pulvinar rhythm every nine periods to give results similar to those reported here. Ultradian rhythms occur in Phaseolus (Millet et al, 1984) and may be coupled to the same oscillator regulating circadian rhythms. If circadian rhythms in P. vulgaris are regulated by a single ultradian oscillator, however, there must be different coupling factors interacting between the oscillator and the overt rhythms to yield different free-running periods.…”
Section: Discussionmentioning
confidence: 99%